INTERACTIVE ENVIRONMENT FOR MASSIVE NEUROSCIENCE SIMULATIONS IN GRID - Salnikov, Andrii; Sudakov, Oleksandr; Levchenko, Roman; Sliusar, Ievgen; Savchenko, Anton (International Journal of Computing, 2014)
End-user oriented system for massive computations in grid is proposed and implemented. The system provides support of user interfaces for input and output data staging, asynchronous jobs submission and control, tasks status and results monitoring. The main system components include web-portal, authentication components and jobs submitter that interact with grid infrastructure. The main advantages of described grid-portal are flexibility in computations back-ends support and possibility to interactively handle thousands of jobs. The proposed integrated environment was implemented in Ukrainian National Grid (U NG) infrastructure for massive simulations of non-linear dynamics in neuroscience.